Penerapan Sistem Pendukung Keputusan Pemilihan Ban Sepeda Motor Honda Dengan Metode Multi Objective Optimization on The Basic of Ratio Analysis (MOORA) - Ari Andini; Gusnia Ariyanti Lestari; Isnaini Mawaddah; Khasanah Khasanah (JURIKOM (Jurnal Riset Komputer), 2018)
Decision support systems are part of computer-based information systems (including knowledge-based systems). Which is used to support decision making in a system. The decision support system provides a semi-structured decision, where no one knows exactly how decisions should be made. The selection of Honda motorcycle tires always provide the best quality to costumer for use on motorcycle vehicles. To get the best quality costumer needs a decision support system. In this study, the authors apply the method of Multi Objective Optimization On The Basic Of Ratio Analysis (MOORA Method) as a method to be applied in decision support system.